The Status of Mental Disorder and to Identify the Barriers of Psychological Treatment among University Student - Saha, Diba; Siddique, Nur-E-Alam (Asian Journal of Interdisciplinary Research, 2024)
Depression, anxiety, and stress are widespread mental health concerns among modern university students, and these conditions appear to be increasing. This study aimed to examine the prevalence of mental health issues, and also to identify the barriers of psychological treatment. The study's sample size was 344 students drawn at random from Rajshahi University. To assess the extent to which the participants suffered from mental illness, the Bangla version of the Depression Anxiety, and Stress Scale (DASS-21) was administered, and the translated Bangla adaptation of Perceived Barriers to Psychological Treatment Scale (PBPT) was also applied to the same participants to identify the barriers of psychological treatment. The acquired data were analyzed with descriptive statistics in IBM SPSS Version 25.0. It was determined that 50.57% of respondents demonstrated moderate to extremely severe stress symptoms, 72.97% of students exhibited moderate to extremely severe anxiety symptoms, and 56.7% exhibited moderate to extremely severe depressive symptoms, respectively. Study participants cited two major barriers to seeking mental health treatment: a lack of available services (51.5%) and the difficulty in finding a counselor (41.3%). This study helps in understanding the mental states of students and planning activities related to offering counseling services.